(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
analgesic administration as well as between early and delayed epidural analgesia. Monitoring was done to identify if any complications occur either due to the procedure or anaesthetic or analgesic drug itself. Results: A total number of 100 patients were recruited for this study. Following thoracic epidural analgesia (TEA), pain rating improved in 76.0% cases; coughing was diminished in 78.0% cases, while suctioning was improved in 68.0% cases. Besides, physiotherapy and positioning improvement were found in 68.0% cases and 72.0% cases respectively, while chest expansion was improved in 88.0% cases. Thoracic epidural analgesia was given soon after injury and had given a significant improvement compared with the patients who got the delayed TEA considering in ventilation (78.0% vs. 22.0%) and in mobilization (72.0% vs. 32.0%)(p<0.001); however, weaning from the ventilator or length of ICU stay had no difference among those two groups. Moreover, pneumonia, acute respiratory distress syndrome (ARDS) and mortality reported more in those who got delayed TEA(p<0.05). Complications included the misplacement of catheter (2.0%), hypotension (8.0%), bradycardia (6.0%) and respiratory depression (2.0%). Conclusion: Thoracic epidural analgesia which is given soon after injury has showed better prognosis and outcomes in the patients suffering from multiple rib fractures with neurotrauma. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 24-28